Study of the transportable Energy Storage System (TESS) based on a time space network method - Tan, Puay Jun (Nanyang Technological University, 2020)
This report aims to discuss the potential uses of Transportable Energy Storage System (TESS) in enhancing resilience in Distribution Systems (DS) in the events of a catastrophe. A Joint Post Disaster Restoration Scheme is introduced in this report and it aims to help minimize the total system cost in terms of customer interruption cost, generation cost, and TESS related costs. This scheme is presented as a Mixed Integer Linear Programming (MILP) model taking into consideration of the various operation constraints such as the TESS, DS constraints. The proposed scheme uses a 33-bus distribution system having three MGs and four TESSs.